Determinants of oral self-care in the Brazilian adult population: a national cross-sectional study - Bordin, Danielle; Fadel, Cristina Berger; Santos, Celso Bilynkievycz Dos; Garbin, Cléa Adas Saliba [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Saliba, Nemre Adas [UNESP] (FapUNIFESP (SciELO), 2017)
This study aims to investigate variables related to adherence to oral self-care in the Brazilian adult population. It is an exploratory study, using secondary data from a population-based survey on a representative sample of the adult population of the entire Brazilian territory (n=60202). The sample was selected using a multiple stage approach. The oral self-care indicator was defined by grouping the variables: periodicity of dentist appointments, use of dental floss, toothbrush and toothpaste, frequency of brushing and replacement of the toothbrush. The scores obtained from the indicator were categorized into adequate, partially adequate, and inadequate care. Statistical analysis consisted of dimensionality reduction, and oral self-care-related variables were submitted to logistic regression. The variables mostly related to inadequate or partially adequate oral self-care were: illiteracy (OR = 11.20, OR = 4.81), low educational level (OR = 3.50, OR = 1.96), negative oral health self-concept (OR=3.73, OR=1.74), absence of natural teeth (OR = 4.98, OR=2.60), edentulous lower arch (OR = 3.09; _____), number of missing upper teeth (OR=1.14, OR=1.05), absence of health insurance (OR=2.23, OR=2.07), sedentary lifestyle (OR=2.77, OR=1.51), and smoking (OR=2.18, OR=1.40). It was concluded that the individual's level of education is one of the main factors for adherence to adequate oral self-care, followed by level of oral health self-concept and tooth loss. Likewise, lifestyle also bears a significant influence.